Pensamento algébrico e equações no ensino fundamental: uma contribuição para o Caderno do professor de matemática do oitavo ano - Silva, Antonia Zulmira da (2012)
The purpose of this investigation was to find evidence of indicators of algebraic thinking development for the topic 'First-degree algebraic equations' from the mathematics Teacher's Manual adopted by public middle schools in São Paulo state, Brazil, and thus provide a written contribution to this teaching material. The investigation sought to answer the following research questions: Do the activities proposed in the topic 'First-degree algebraic equations' from the mathematics Teacher s Manual for the third quarter of the eighth grade enable teachers to foster the development of algebraic thinking among students? If so, which indicators are most evident? The definition used for indicators of algebraic thinking development drew on Fiorentini, Miorim, and Miguel (1993) and Fiorentini, Fernandes and Cristóvão (2005) with regard to aspects of algebraic thinking and on Ursini et al. (2005) concerning use of variables. Concurrently, the so-called multimeanings of equations, as defined by Ribeiro and Machado (2009), were taken into account. Desk research, as defined by Lüdke and André (1986), was the method selected for the study. Of the twelve indicators of algebraic thinking development investigated, nine were detected in the activities examined. The results obtained showed that these activities enable teachers to foster the development of algebraic thinking among students. A final, stand-alone section summarizes the theoretical framework adopted and includes a chart of the algebraic thinking indicators investigated, in addition to a synthetic view of the analyses providing evidence of these indicators in the activities. This summarized section is also available in CD-ROM format